The effectiveness of aloe vera gel versus 2% chlorhexidine gluconate in preventing phlebitis from peripheral venous catheters: A randomized controlled trial - Mahdiyeh Harati Nassab; Mozhgan Rahnama; Abdolghani Abdollahimohammad; Mahin Naderi Far (Journal of Research Development in Nursing and Midwifery)
Background: While intravenous injections are essential in life-saving situations, their routine use can lead to various complications, particularly phlebitis, which negatively impacts patients' physical and psychological health. This research aims to evaluate the effectiveness of topical aloe vera gel compared to 2% chlorhexidine gluconate in preventing phlebitis associated with peripheral venous catheters. Methods: This three-arm randomized controlled trial, executed in 2024 at a university-affiliated hospital situated in southern Iran, enrolled 90 hospitalized individuals receiving intravenous therapy. The study employed convenience sampling for participant recruitment, followed by permuted block randomization with a block size of six to allocate participants into three distinct groups, each comprising 30 patients. Aa (aloe vera group): Disinfection with 70% alcohol, and the catheter fixation with an adhesive dressing impregnated with aloe vera gel; Bb (chlorhexidine group): Disinfection with 70% alcohol and chlorhexidine, followed by fixation with a chlorhexidine-impregnated adhesive dressing; and C (control group): Disinfection with 70% alcohol and standard adhesive dressing. The catheter insertion site was systematically evaluated for the incidence of phlebitis using a standardized phlebitis checklist at discrete time points: 12, 24, 36, 48, 60, and 72 hours post-sampling. Statistical analysis of the collected data was performed employing SPSS version 25 statistical software. A significance threshold of α = 0.05 was adopted for all statistical tests, which included Chi-square tests and one-way analysis of variance (ANOVA). Results: At 72 hours post-intervention, the incidence of phlebitis demonstrated a statistically significant disparity between the groups (p = 0.005). Conversely, no significant intergroup differences were evident in the manifestation of phlebitis symptoms at the 12-hour (p = 0.999), 24-hour (p = 0.493), 36-hour (p = 0.493), 48-hour (p = 0.186), and 60-hour (p = 0.064) time points after the intervention. Specifically, out of 30 participants in the aloe vera group, 12 (40%) remained asymptomatic for phlebitis—defined by the absence of redness, edema, pain, and vein induration—up to the 72-hour assessment. In comparison, the chlorhexidine group exhibited 5 (16.7%) patients, while the control group presented with only 2 (6.7%) patients who did not display phlebitis symptoms during this period. Conclusion: Based on the observed outcomes, nurses may consider using aloe vera gel to reduce phlebitis in patients requiring catheterization for more than 48 hours, due to its anti-inflammatory properties and non-pharmacological benefits. However, this recommendation should be approached cautiously, pending further rigorous research to validate these initial findings and develop standardized guidelines. Future studies should investigate the long-term effects of aloe vera gel, compare its effectiveness with other interventions, and assess patient outcomes in various clinical settings to better understand its role in preventing phlebitis.